PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP PERILAKU INOVATIF PEGAWAI SMK NASIONAL BERBAH - Wahyu Dea Endarwati; E. Didik Subiyanto; Epsilandri Septyarini (J-MACC, 2022)
The motivation behind this review is to decide whether there is an impact of leadership style on innovative behavior, decide whether there is an impact of the work environment on innovative behavior, decide whether there is an impact of job satisfaction on innovative behavior and decide whether there is an impact of leadership style, work environment and job satisfaction on innovative behavior simultaneously on employees. Berbah National Vocational School, Sleman, Special Region of Yogyakarta. With a population of 50 employees of the Berbah National Vocational School with a saturated sampling method. The method of data collection is done by distributing questionnaires, this research is descriptive quantitative. The analytical methods in this study are instrument test (validity and reliability), classical assumption test, multiple linear regression analysis and t test and F test. The results of this study indicate (1) leadership style has a negative and significant impact on innovative behavior, (2) The work environment has a negative and significant impact on innovative behavior, (3) Job satisfaction has a positive and significant impact on innovative behavior, and (4) Leadership style, work environment and job satisfaction have a simultaneous impact on innovative behavior.